2017
DOI: 10.20884/1.jm.2017.12.2.324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH and Aging Time on the Synthesis of TiO2 – Chitosan Nanocomposites as Photocatalyst by Sol-Gel Method at Room Temperature

Abstract: The synthesis of TiO 2 -chitosan nanocomposite photocatalyst using Titanium(IV)-Isopropoxide (TTIP) as precursors and chitosan as host material has been conducted. The synthesis was carried out using a sol-gel method at room temperature and aging to grow crystal seeds and generate nanoparticles. The success of forming nano-sized anatase phase TiO 2 nanocrystal was strongly influenced by the sol pH system during hydrolysis and the aging time. The effect of sol pH system and aging time to the crystallinity level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Chitosan could also adsorb Cu(II) through the formation of chelates with active groups -NH2 (Inger, Volda, Eric, & Olav, 2003;Guibal, 2005). The type 0.13 of TiO2-chit nanocomposite provided the highest adsorption capacity (qe = 3.22 x 10 2 mg/g) because of the highest chitosan availability (Fajriati et al, 2017).…”
Section: Effects Of Contact Timementioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan could also adsorb Cu(II) through the formation of chelates with active groups -NH2 (Inger, Volda, Eric, & Olav, 2003;Guibal, 2005). The type 0.13 of TiO2-chit nanocomposite provided the highest adsorption capacity (qe = 3.22 x 10 2 mg/g) because of the highest chitosan availability (Fajriati et al, 2017).…”
Section: Effects Of Contact Timementioning
confidence: 99%
“…It was characterized by the separation of the electron-filled valence band and the empty conduction band with a bandgap energy of 3.07 -3.19 eV. TiO2chitosan nanocomposite demonstrates an absorption edge ranging from 300 to 450 nm, which corresponds to absorption edge of semiconductor material (Fajriati, Mudasir, & Wahyuni, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 particles outside the chitosan matrix had a large particle size because they were aggregated. This had caused the light absorbed by TiO2 to be partly because the one exposed to light was the surface of TiO2 only [19].…”
Section: The Effect Of Tio2 Weight In Photodegradation Processmentioning
confidence: 99%
“…Table 4 showed that the highest observed kinetic (kObs) was achieved by TiO2/Chit 0.65, while the highest corrected kinetic (k) was achieved by TiO2/Chit 1.3. The TiO2/Chit 0.65 nanocomposite had the highest observed kinetic (kObs) because it has the highest Eg value and the highest crystallinity [19]. On the other hand, the TiO2/Chit 1.3 nanocomposite had the highest corrected kinetic (k) because the adsorption equilibrium constant (kL) value of TiO2/Chit 1.3 was the lowest, hence the time needed by dyes to achieve the adsorption equilibrium on the TiO2/Chit 1.3 nanocomposite was shorter.…”
Section: The Kinetics Of Mo and Mb Photodegradationmentioning
confidence: 99%
“…The study on the removal of low molecular weight compounds by photocatalyst for reuse of electronics wastewater was relatively unexplored, while the development of an efficient AOP technology has a great impact on the expansion of the reuse process. In addition, it is challenging to immobilize photocatalysts in the sol-gel method with good morphology, photochemical activity, and mechanical stability due to many factors, such as concentration of the precursor, water to precursor ratio, pH, aging time, and calcination conditions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%